2022
DOI: 10.3390/medicina58111593
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphism of the Methyl Tetrahydrofolate Reductase (MTHFR) Gene with Anti-Seizure Medication Response in Pediatric Patients in Jeddah, Saudi Arabia

Abstract: Background and Objectives Epilepsy is a chronic brain disease, with inherent and noninherent factors. Although over 20 anti-seizure medications (ASMs) are commercially available, nearly one-third of patients develop drug-resistant epilepsy. We evaluated the association between the clinical features and the methyl tetrahydrofolate (MTHFR) rs1801133 polymorphism and ASMs response among pediatric patients with epilepsy. Materials and Methods This was a multicenter, retrospective, case–control study of 101 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The possible pathogenic mechanism by which Hcy causes damage to blood vessels are: damage to the endothelium of the blood vessels, encouragement and participation in oxidative metabolism of Low Density Lipoprotein (LDL), increased platelets aggregation mediated by thromboxane, inhibition of thrombomodulin expression on cell surface and activation of protein C, improved binding of lipoprotein to fibrin, amplify smooth muscle cell proliferation and collagen accumulation [47][48][49][50]. Studies has suggested a con-Volume 08; Issue 03 J Urol Ren Dis, an open access journal ISSN: 2575-7903 nection between MTHFR gene polymorphisms, especially C677T and A1298C (rs 1801131), and several pathological conditions, including kidney disease, cardiovascular disease, neural tube defects, cancer, inflammatory bowel disease, type 2 diabetes, Down syndrome, headache, epilepsy, Alzheimer's disease, schizophrenia, liver diseases, and numerous chronic diseases and disorders of regulation of embryonic development [51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…The possible pathogenic mechanism by which Hcy causes damage to blood vessels are: damage to the endothelium of the blood vessels, encouragement and participation in oxidative metabolism of Low Density Lipoprotein (LDL), increased platelets aggregation mediated by thromboxane, inhibition of thrombomodulin expression on cell surface and activation of protein C, improved binding of lipoprotein to fibrin, amplify smooth muscle cell proliferation and collagen accumulation [47][48][49][50]. Studies has suggested a con-Volume 08; Issue 03 J Urol Ren Dis, an open access journal ISSN: 2575-7903 nection between MTHFR gene polymorphisms, especially C677T and A1298C (rs 1801131), and several pathological conditions, including kidney disease, cardiovascular disease, neural tube defects, cancer, inflammatory bowel disease, type 2 diabetes, Down syndrome, headache, epilepsy, Alzheimer's disease, schizophrenia, liver diseases, and numerous chronic diseases and disorders of regulation of embryonic development [51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%